Avaliação clínica de uma solução líquida de éter gliceril guaiacol (EGG) pronta para uso em anestesia de grandes animais - Hellú, José Abdo de Andrade (2009)
The 3-(2-Metoxifenoxi)-1,2-propanediol, also known as guaifenesin, guayacol glyceryl ether or simply GGE is a myorelaxant drug used by veterinarian to induce recumbency in equines by intravenous infusion in a 10% water solution. Conventionally, this solution is prepared in loco few moments before its application due to its instability to the ambient temperature, causing relative risks to the handling of the product and also due to its lack of sterility. The main objectives of this study were to evaluate the clinical efficiency and any undesirable effects of intravenous injection of a solution of guayacol glyceryl ether, at a concentration of 10% in horses, assess the compatibility of the solution developed with xylazine and ketamine and compare the cardiorespiratory effects caused the use of the combination of xylazine and ketamine, with the solution and the solution of SRU-GGE. This study describes and compares the parameters: heart rate, respiratory rate, mean arterial pressure, oxyhemoglobin saturation, and rectal temperature, obtained before, during and after the application of solutions prepared at the moment of application, of solutions ready for use (SRU) and Triple Drip (GGE solution ready for use in association with xylazine and ketamine). Moreover, too were recorded and compared the time elapsed between pre-anesthetic medication and anesthetic induction, time of administration of the solutions, the latency period for the decubitus, the time elapsed between the end of the administration of the solutions and the and the moment in wich the animals adopted the sternal recumbency, the time elapsed between the end of the administration of solutions and the time when the animals recovered the quadrupedal position. Finally it was presented the formulation developed for anesthesia of large animals, as well as its clinical efficiency and pharmacological activity. Key words: guaifenesin, horses, xylazine, ketamine and clinical evaluation